KINERJA KEUANGAN DITINJAU DARI RASIO KEUANGAN PEMERINTAH DAERAH KOTA KEDIRI TAHUN ANGGARAN 2018-2021 - Fadhilah, Aulia Nuril (Universitas Nusantara PGRI Kediri, 2022)
This study is intended to measure the financial performance of the Kediri City Government in 2018-2021 in terms of the ratio of effectiveness, efficiency, independence, activity and growth. The approach and analysis technique used is descriptive quantitative. Secondary data collection using the method of documentation. The results showed that the financial performance of the City of Kediri in terms of the effectiveness ratio is classified as very effective at 121,98%. The efficiency ratio of 94,74% is considered less efficient. The independence ratio of 29,86% is considered low. The activity ratio consists of operating expenditure of 87,05% and capital expenditure of 10,19%. The growth ratio is positive, but the growth of PAD, revenue and capital expenditure is negative in 2019-2020. There are several studies that examine government financial performance, but researchers argue that different places and years of research included novelty.